2018
DOI: 10.3390/molecules23071536
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Intracellular Delivery of Cell-Impermeable Cargo Molecules by Peptides Containing Tryptophan and Histidine

Abstract: We have previously evaluated and reported numerous classes of linear and cyclic peptides containing hydrophobic and hydrophilic segments for intracellular delivery of multiple molecular cargos. Herein, a combination of histidine and tryptophan amino acids were designed and evaluated for their efficiency in intracellular delivery of cell-impermeable phosphopeptides and the anti-HIV drug, emtricitabine. Two new decapeptides, with linear and cyclic natures, both containing alternate tryptophan and histidine resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In recent years, synthetically engineered cyclic peptides have been utilized as drug delivery systems for transporting various types of molecular cargos such as anticancer drugs and siRNAs [16]. The cyclic nature of peptides has been discovered to be critically important to enhance their intracellular transporting efficiency [17][18][19]. We introduced a class of homochiral L-cyclic peptides with enhanced potency in nuclear targeting delivery of anti-HIV drugs and biomolecules [20].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, synthetically engineered cyclic peptides have been utilized as drug delivery systems for transporting various types of molecular cargos such as anticancer drugs and siRNAs [16]. The cyclic nature of peptides has been discovered to be critically important to enhance their intracellular transporting efficiency [17][18][19]. We introduced a class of homochiral L-cyclic peptides with enhanced potency in nuclear targeting delivery of anti-HIV drugs and biomolecules [20].…”
Section: Introductionmentioning
confidence: 99%
“…After excluding cyclic peptides and CPPs that had un-natural residues or amino acids with D-conformations, 1155 unique CPPs remained. Although some of the excluded CPPs—CPPs with unnatural or D-conformation residues and cyclic CPPs—have shown promising results in experimental studies [81,82,83], current computational web servers are unable to analyze these sequences. Mature CPG2 amino acid sequence from Pseudomonas sp.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported the application of cyclic CPPs containing alternatively positively charged arginine and hydrophobic tryptophan residues, [WR] 4 and [WR] 5 , as drug delivery tools and nuclear targeting tools in 2011 [ 209 ]. Several other monocyclic CPPs were engineered based on this template and were shown to be efficient molecular transporters for enhancing the efficacy of existing chemotherapeutic, antiviral, and antibacterial agents [ 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ]. The monocyclic CPPs containing tryptophan and arginine residues were also used to conjugate with potential therapeutic agents.…”
Section: Peptide-based Therapiesmentioning
confidence: 99%
“…Adding to the previous work, we also demonstrated that several monocyclic peptides containing cysteine and arginine residues, such as cyclic [CR] 4 , significantly enhanced the cellular uptake of a cell-impermeable phosphopeptide (F’)-Gly-(pTyr)-Glu-Glu-Ile (F’-GpYEEI) in the presence of endocytic inhibitors and sodium azide in the lymphoblastic leukemia cell line (CCRF-CEM) [ 218 ]. Furthermore, tryptophan and histidine-containing cyclic decapeptides [WH] 5 demonstrated an increase of the intracellular delivery of a cell-impermeable phosphopeptide and an anti-HIV drug, emtricitabine [ 217 ]. In another effort, monocyclic [HR] 4 peptides were used as a molecular transporter and were able to double the permeability of F’-GpYEEI in human ovarian adenocarcinoma cells (SK-OV-3) cells [ 214 ].…”
Section: Peptide-based Therapiesmentioning
confidence: 99%